PERANCANGAN BUSANA EVENING DARI BAHAN BATIK NITIK SUMBER IDE RATIMAYA NITIK - Mrs Jumariah; Tri Utami (Jurnal Socia Akademika, 2021)
ABSTRACTThis research aims to: 1) apply the source of Ratimaya Nitik's idea in the manufacture of evening fashion; 2) know how the process of making evening fashion from batik nitik kembang telo with cotton and organza; 3) apply embroidery application with sequin decoration in the manufacture of evening fashion from batik nitik material with the source of the idea Ratimaya Nitik. Research methods use experimental methods. The subject of the study was evening fashion from batik nitik material with the source of ratimaya nitik ideas combined with cotton and organza with embroidery and sequin pplication decoration. The stages of experimentation are making design, taking body size, pattern making, cutting materials, sewing and finishing. Sensory tests conducted against panellists aim to find out the reaction of panellists to the design of evening fashion reviewed from the aspect of the application of the source of ideas with criteria aspects of principles and elements of design and harmony of decoration. Based on the results of sensory tests, aspects of the application of the source of ideas, principles and elements of design as well as embroidery application decoration is stated to be suitable. The combination with organza material is stated to be quite good because the nature of organza material is a bit stiff so less fall